Gamification in halal context: theory and potentials - Ahmad, Anis Najiha; Ahmad, Izzah Az Zahra; Hashim, Yumi Zuhanis Has-Yun; Samsudin, Nurhusna; Zulkurnain, Musfirah (Springer Singapore, 2024)
Gamification is an informal umbrella term for the use of video game elements in non-gaming systems. Gamification is a method of motivating and changing behaviors. It has been successfully applied in multiple sectors, including health, tourism, hospitality, banking, manufacturing, and education, for multiple purposes. It is widely used for customer-facing approaches such as marketing, brand advocacy programs, and loyalty programs. In an organization, it is used to design employee experiences, employee onboarding, employee engagement, and talent acquisition. A gamification project might also be tailored to improve learning and development. Despite its potential, gamification is appallingly underused in the halal context. The chapter aims to initially introduce the potential applications of gamification within the halal industry ecosystem, with the theoretical aspects being introduced later in the chapter, for a gradual buildup. Examples of gamification applications for multiple halal stakeholders, such as the halal industry, education and training providers, and authorities, are included. The chapter concludes by highlighting a practical demonstration of gamification's real-world applicability within the halal context, using the six Ds framework in the development of “Halal Inspector Mastery.”